PEMBINAAN KINERJA GURU DENGAN MEMAKSIMALKAN MANAJEMEN KOMUNIKASI KEPALA MADRASAH DI MTS NURUL KHAIRIYAH - Novita Sari (Hijri, 2021)
The purpose of this study is to see how teacher performance is fostered by maximizing the communication management of the madrasa principal at MTs Nurul Khairiyah, this research method is qualitative. This series of management processes communicate the principle of madrasah in educational institutions such as planning, organizing, implementing, and supervising. Communication activities at MTs Nurul Khairiyah are interactions between the principal and teachers, as well as other staff who are involved in madrasa education in order to carry out managerial activities in order to achieve superior success.Performance Coaching, Management, Communication